Prediction of ovarian aging using ovarian expression of BMP15, GDF9, and C-KIT. Issue 8 (April 2020) - Park, Min Jung; Ahn, Jun-Woo; Kim, Ki Hyung; Bang, Junghee; Kim, Seung Chul; Jeong, Jae Yi; Choi, Ye Eun; Kim, Chang-Woon; Joo, Bo Sun
This study investigated ovarian expressions of bone morphogenetic protein 15 (BMP15), growth differentiation factor 9 (GDF9), and C-KIT according to age in female mice to determine whether these factors can be served as new potential biomarkers of ovarian aging. Ovaries were collected from mice aged 10, 20, 30, and 40 weeks, and ovarian expressions of BMP15, GDF9, and C-KIT were examined by real-time PCR, Western blot, and immunohistochemistry. Follicle counts were measured on histological hematoxylin and eosin staining. In the second experiment to evaluate ovarian function, after superovulation with PMSG and hCG, the numbers of zygotes retrieved and embryo development rate were examined. Ovarian expressions of BMP15, GDF9, and C-KIT decreased with age. Follicle counts, numbers of retrieved zygotes, and embryo development rate were also significantly reduced in old mice over 30 weeks compared with young mice. These results indicate that these factors could be served as new potential biomarkers of ovarian aging. Impact statement: Ovarian aging is becoming a more important issue in terms of fertility preservation and infertility treatment. Serum anti-Mullerian hormone (AMH) level and antral follicle count (AFC) are being practically used as markers of ovarian aging as well as ovarian reserve in human. However, these factors have some drawbacks in assessing ovarian aging and reserve. Therefore, the identification of ovarian expressions of BMP15, GDF9, and C-KIT according to female could be applied as a potent predictor of ovarian aging. This work provides new information on the development of diagnosis and treatment strategy of age-related fertility decline and premature ovarian insufficiency.